Effects of Rhubarb on Intestinal Dysmotility in Critically Ill Patients - Shimizu, Kentaro; Kageyama, Mitsuru; Ogura, Hiroshi; Yamada, Tomoki; Shimazu, Takeshi (Internal Medicine, 2018)
Intestinal dysmotility is a major problem in critically ill patients. This report describes the successful treatment of intestinal dysmotility with rhubarb as a laxative in six critically ill patients on mechanical ventilation. Bowel movement and defecation occurred in all patients an average of 1.8 days after the administration of powdered rhubarb. In 4 patients who also had gastric reflux, the reflux volume via nasal tube was decreased an average of 3.5 days after the initiation of rhubarb treatment, and enteral nutrition was able to be started. Rhubarb may be useful for the treatment of incompetent gastric and intestinal motility in critically ill patients.